Studenternas representanter : En kvantitativ studie av samband mellan socioekonomisk bakgrund och engagemang i studentkåren - Ringhage Kechid,Linnea (2020)
In Swedish higher education, the students have a right by law to partake in the decisions that concern them and the education. The participation in such decisions is organized through student representatives elected by the student unions. Previous studies on representation in student unions and politics suggested that a certain socioeconomic background might be overrepresented among the student unions. This motivated a study of who the students’ representatives are. The aim of this study has been to investigate the relation between socioeconomic background and participation in the student union. This was done through a survey that was analysed quantitatively by creating two respective indexes from multiple indicators, measuring socioeconomic background and level of participation in the student union. The correlation and regression between these two indexes was analyzed through Bourdieu’s theoretical framework of different types of capital and field. The study found a very weak correlation, however not statistically significant. This could in parts be explained by the troubles the study had with attrition. Nonetheless does this indicate that there are other reasons, yet to be discovered, behind a person's decision to get involved in the student union and be part of the mobilization of this particular type of clients.
Keywords: student union; representation; student representatives; Bourdieu; field; socioeconomic background